Behavior of Olive Genotypes Against Quick Decline Syndrome (QDS) Caused by Xylella fastidiosa subsp. pauca in Apulia - Mariangela Carlucci; Michele Antonio Savoia; Pompea Gabriella Lucchese; Valentina Fanelli; Isabella Mascio; Francesco Luigi Aurelio; Monica Marilena Miazzi; Andrea Pacifico; Cinzia Montemurro; Franco Nigro (Plants)
Xylella fastidiosa subsp. pauca (Xfp), a quarantine pathogen in the European Union, severely threatens Mediterranean olive production, especially in southern Italy, where Olive Quick Decline Syndrome (OQDS) has devastated Apulian olive groves. This study addresses the urgent need to identify resistant olive genotypes by monitoring 16 potentially tolerant genotypes over six years, assessing symptom severity and bacterial load. These genotypes, which survived in heavily infected areas, showed varied responses to Xfp; some maintained low symptom severity with minimal bacterial presence (high or undetectable Cq values), while others exhibited increased bacterial loads yet remained asymptomatic or showed limited canopy desiccation. SSR markers were used to investigate the genetic relationships among these genotypes and other widespread Mediterranean cultivars, showing genetic similarity with the resistant ones such as the Albanian Kalinjot and the Greek Leucocarpa, as well as with local Apulian cultivars, highlighting the potential of local and Mediterranean olive germplasm for Xfp resistance. This study integrates phenotypic responses with genetic knowledge to support the development of conservation strategies that will enhance the genetic diversity of Apulian olive cultivars. In addition, by focusing on the resilience of the different olive genotypes, this research aims to protect the traditional cultivars from the emerging threats, thus preserving the ecological and cultural heritage of the olive biodiversity of the Mediterranean region.